Behind networks knowledge transfer, favor exchange and performance - van der Eijk, Adriaan Rene; Dolfsma, W.A. (Wilfred); van de Velde, S.L. (Steef); Erasmus Research Institute of Management (Rotterdam Erasmus Research Institute of Management, Erasmus University Rotterdam, 2009)
"The value of knowledge for economic development can hardly be overstated as it essentially determines what organizations do as well as how they do it. Ensuring firm survival yields fierce competition, requiring organizations to continually improve their product and operations. That is, upgrade their knowledge base and develop new knowledge on how to do the right things more efficiently. Managing organizational knowledge and stimulating its development means that firms must carefully consider their knowledge development and diffusion strategies. Doing so, as this book argues, requires practitioners to realize that knowledge development and diffusion is a social cooperative process. At its most basic level new knowledge is created as a result of human interaction. Knowledge is shared between individuals and is fueled by micro-objectives and motivations. Applying a micro perspective, this book posits that knowledge exchange resembles the exchange of gifts. It follows that professional networks, as the conduits through which knowledge is exchanged, are an important determinant for scientists performance. Utilizing the full potential of organizational scientific and human technical capital requires firms to map, shape and encourage individual network formation."--publisher.
Includes bibliographical references.
Keywords: Knowledge management; Organizational learning; Social network analysis